O número de ouro no ensino da matemática na educação básica - Silva, Luiz Henrique Morais da [UNESP] (2013)
The goal of this work is to bring new activities (theoretical and practical), around a single subject (The Golden Number), to be exploited in several existing content in the current mathematical curriculum at school. From this subject, we introduce the idea of extreme and mean ratio, as well the concept of the Golden Ratio, so, we expect that students can be able to get the Golden Number and understand their mathematical properties and their applications (related to Golden Triangle and Golden Rectangle)